Music-induced Mood Biases Decision Strategies during the Ultimatum Game - Chung, Hwanjun; Lee, Eun Jung; Jung, You Jin; Kim, Sang Hee (Frontiers in Psychology, 2016)
Recently, an increasing attempt has been made to understand the influence of mood on socioeconomic decision-making. We tested in this study whether an unpleasant mood would lead to unfavorable decisions more frequently than a pleasant mood, and whether decisions under different moods can be explained in different ways. Healthy volunteers were assigned to either a pleasant or unpleasant mood group and listened to musical excerpts to induce pleasant or unpleasant mood. Both groups completed the ultimatum game as a responder with an unacquainted partner who was actually a confederate. The proposer’s offers were made in six different ratios of split (1:9, 2:8, 3:7, 4:6, 5:5, 6:4) in a preprogramed manner unbeknownst to the participants. After the completion of the task as a responder, the participant rated subjectively perceived fairness and emotional feelings about each split of offer. The statistical results showed that the unpleasant mood group rejected unfair offers more often compared to the pleasant mood group. Self-reported ratings of perceived fairness and emotional feelings did not statistically differ between the two groups. Interestingly, however, only in the unpleasant mood group, rejection rates of unfair offers were negatively correlated with perceived fairness. Both the pleasant and unpleasant mood groups showed a negative correlation between rejection rates of unfair offers and self-reported happiness. These results suggest a possibility that different decision strategies operate under different mood during a socioeconomic exchange.